PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN DAN IMPLIKASINYA PADA KINERJA KARYAWAN (KASUS PADA PT PERMATA BANK TBK) - Cicih Ratnasih; Suyanto Anibala Riwu (Jurnal Manajemen FE-UB, 2018)
This study aims to determine the influence of leadership style and Motivation on employee productivity in the Department of Account Services. The data used in this study is Primary Data collected from the results of distributing Questionnaires conducted on the Department of Account Services, data management methods using Path Analysis Method (Path Analysis) using SPSS application program version 22, and sample used as many as 75 people.            The results showed that there is a positive and significant influence between leadership style and motivation on work productivity. This is evidenced from the results of previous statistical tests. And from the test results also confirmed that the motivation mediates some of the leadership style to work productivity. Keywords: Leadership Style, Motivation, Employee Productivity.